The social consequences of the increase in refugees to Germany 2015-2016 - Marco Giesselmann; David Brady; Tabea Naujoks (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2021)
More than one million refugees migrated to Germany in 2015-2016. The increase in refugees was rapid, visible and controversial, and varied substantially across German districts. Therefore, the increase provides unique leverage for analyzing the consequences of immigration and ethnolinguistic heterogeneity. We innovatively focus on within-district/within-person change with individual-level panel data and precise measures of district-level refugee shares. Using the German Socio-Economic Panel 2009-2017, we analyze three-way (person, year and district) fixed effects models of five exclusionary beliefs and behaviors. At the national level, concerns about immigration and social cohesion and strong far right party support increased at the same time as refugee shares increased. However, district-level refugee shares are robustly negatively associated with concerns about immigration and (less robustly) with strong far right party support. They are also not associated with concerns about social cohesion, residential moves, or subjective fair tax rates. Interaction estimators reveal that where unemployment is high, there are positive relationships between refugee shares and concerns about immigration and residential moves. Aside from high unemployment districts however, the results mostly support contact theory, and contradict fractionalization and minority threat theories. Overall, rising district-level refugee shares reduced or at least did not heighten exclusionary beliefs and behaviors.
Keywords: 320